Computers versus Partnering: A Look at Student Mathematics Achievement - Coleman, Belinda (Valdosta State University, 2004)
This action research project identified and compared the differences between using partner practice and computer practice on students' test scores, reactions, and time on task while working on the guided practice segment of daily math lessons. A review of the literature revealed that both learning strategies were recommended for middle school students. However, more support was found for the use of computers in helping to increase student achievement than for partnering. Two classes of seventh grade students participated in this study, which took place over approximately a month. Students completed two chapters of study with the same instruction from the teacher and the same textbook. Students in one class used the computer software while the other class used the partnering technique during the practice segment of the lesson. During the next chapter, students exchanged strategies. End-of- Chapter tests and quizzes were given to measure differences in achievement. Students were also observed throughout the practice time to identify behaviors exhibited during the practice segment of the lesson. Based upon the quiz and test data, observations, and surveys, computers improved student achievement and time-on-task more than partnering. However, the increase was small and should be further tested. The results of this action research project were communicated to fellow mathematics teachers through a learning community celebration. The teachers agreed the computer program would be a beneficial part of the mathematics lesson.
Keywords: partner practice; computer practice; math; Educational technology; Teaching--Aids and devices; Computer-assisted instruction